Epilobieae genomes and the evolution of Myrtales - Dan Wang; Wenkai Li; Bing Yang; Yujia Shen; Jun He; Derek W. Dunn; Kang Huang; Baoguo Li (BMC Plant Biology)
Abstract The order Myrtales, one of the most species-rich lineage within the Superrosidae clade, with the majority of its species distributed across five families: Myrtaceae, Melastomataceae, Lythraceae, Onagraceae, and Combretaceae. Despite the ecological and economic importance of the Myrtales, its phylogenetic relationships remain unresolved, with previous studies yielding inconsistent results based on gene fragments and plastid genomes. Genomic data, particularly single-copy/low-copy nuclear genes, provide valuable insights for resolving these phylogenetic relationships. However, phylogenetic studies still lack sufficient clade coverage, particularly for less studied families such as the Onagraceae. Epilobieae is an important tribe of the Onagraceae, characterized by substantial chromosomal number variation and whole genome duplication event (WGD). Nevertheless, the mechanisms of chromosomal evolution remain unresolved. Here, we sequenced and assembled the genomes of two representative species from the Epilobieae, Chamerion angustifolium (formerly Chamaenerion angustifolium) and Epilobium hirsutum, with genome sizes of 636.59 Mb and 400.23 Mb, respectively. Genome evolution analysis revealed two WGD events, during which the chromosome number increased from $$\:\text{n}=9$$ to $$\:\text{n}=18$$ , followed by aneuploid reduction, leading to the diverse chromosomal numbers observed within this tribe. The WGD retained genes are enriched in Environmental information processing pathways, potentially enhancing resistance to biotic and abiotic stresses. These genes also show a preference for multiple exons, which may promote alternative splicing and functional diversification. Additionally, integrating genomic data from 24 Myrtales species, a robust phylogenetic framework based on 994 single-copy/low-copy orthogroups were reconstructed. Our results supported Combretaceae as the sister group to Myrtaceae and Melastomataceae, providing new insights into the evolutionary relationships within the Myrtales.